The Utilization of Aloe Vera (Aloe barbadensis Miller) in Reducing Glucose Levels in Patients with Diabetes Mellitus - Diah Dwi Astuti; Fahmi Romdhoni; Saryono Saryono (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
ABSTRACT Background: Diabetes mellitus is a disease characterized by chronic hyperglycemia and glucose intolerance caused by metabolic disturbances in insulin production, insulin action, or both. Herbal plants might be used to cure this disease. Previous research discovered that herbal plants, such as aloe vera, are more effective at decreasing the risk of diabetes because they have hypoglycemia features and can reduce blood glucose levels. Objective: This systematic review aims to investigate the potential of aloe vera as a dietary additive that can minimize the risk of diabetes, especially diabetes mellitus. Methods: The study's design was a systematic review utilizing the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) technique, which searched for articles published between 2013 and 2023 in electronic databases such as Google Scholar, Pubmed, and Science Direct. These articles were then extracted by analyzing the titles and abstracts for topical relevance. Results: The five articles selected indicate that aloe vera has the potential as an additional food ingredient to reduce blood glucose levels by utilizing aloe vera's hypoglycemic content and maintaining endurance in the body to prevent diabetes. Aloe vera's aloe-emodin content activates insulin and improves the rate of glycogen synthesis, proving it effective for lowering blood sugar levels. In addition to aloe-emodin, aloe vera contains chromium, which helps in the activation of insulin secretion by pancreatic cells and the increased supply chain of glucose into cells by the insulin hormone. As an outcome, it will increase the number of insulin receptors on the cell membrane, enabling insulin to bind to cells. While insulin production increases, glucose production by the liver reduces, and blood glucose drops. Conclusion: As a result, it can be concluded that consuming aloe vera can lower blood glucose levels and thus minimize the risk of diabetes, especially diabetes mellitus. Keywords: Blood sugar levels, aloe vera, type II diabetes mellitus.